PERANAN MANSYURDIN SEBAGAI TOKOH PEJUANG DALAM MEMPERTAHANKAN KEMERDEKAAN DI PEKANBARU TAHUN 1945-1949 - Nurfaizatussolihah Nurfaizatussolihah; Isjoni Isjoni; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Mansyurdin was one of the figures who fought in the defense of the independence of the Republic of Indonesia in Pekanbaru in 1945-1949. Mansyurdin was born in Sungai Limau, Pariaman on January 10, 1923 by parents named Nurdin and Balun. Mansyurdin is the first of five children. During the Japanese occupation, Mansyurdin became the Gyugun army and this is where Mansyurdin received his military training. The aims of this study are: (1) to determine the background to Mansyurdin's life, (2) to determine Mansyurdin's struggle to defend independence in Pekanbaru, (3) to determine the end of Mansyurdin's struggle. The method used in this study is to use a historical methodology with heuristic steps, verification, interpretation and historiography.As a result of this investigation, Mansyurdin's role in defending independence in Pekanbaru began when he brought copies of Bukittinggi proclamation text pamphlets and distributed them to Pekanbaru, after which Mansyurdin formed a youth movement called the Hantu Kubur Union, Mansyurdin was also appointed as deputy commander of the People's Security Front (BKR). which served to defend independence, then Mansyurdin was also involved in the Dutch Military Aggression. After ending the battle in 1945-1949, Mansyurdin was involved in suppressing the Revolutionary Government of the Republic of Indonesia (PRRI) revolt in Riau.Key Words: Mansyurdin, Role, Maintain Independence